2018
DOI: 10.18203/2349-2902.isj20182778
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective clinical study on blunt trauma abdomen and its management

Abstract: Background: Blunt trauma abdomen is a common surgical emergency which may present as an isolated problem or as a part of poly trauma. Road traffic (automobile) accident is the most common cause of blunt trauma abdomen.Methods: After initial resuscitation and achieving hemodynamic stability, all patients were subjected to careful history and clinical examination. Depending on the clinical findings, decision for further investigations as four-quadrant aspiration, X-ray of chest and abdomen erect view and abdomin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 7 publications
1
3
1
Order By: Relevance
“…About half of the patients sustained RTA (48%) followed by assault (30%) and self-fall (22%) in the present study.Anarase and Anarase (2019) also found that road trafc accidents were the predominant cause of trauma. In the study by Rahman and Das (2018), the most common cause of BAT was found to be road trafc accidents (67%) which was slightly higher than the present study. Shah et al (2017) also found that road trafc accident was responsible for 79.4% of blunt abdominal trauma cases.…”
Section: Discussioncontrasting
confidence: 78%
See 1 more Smart Citation
“…About half of the patients sustained RTA (48%) followed by assault (30%) and self-fall (22%) in the present study.Anarase and Anarase (2019) also found that road trafc accidents were the predominant cause of trauma. In the study by Rahman and Das (2018), the most common cause of BAT was found to be road trafc accidents (67%) which was slightly higher than the present study. Shah et al (2017) also found that road trafc accident was responsible for 79.4% of blunt abdominal trauma cases.…”
Section: Discussioncontrasting
confidence: 78%
“…Common surgeries performed in the studied cases included splenectomy (28.57%), primary closure of perforation (23.80%) and resection and anastomosis (19.04%). Rahman and Das (2018) showed that 53.52% of patients having solid organ injured were managed conservatively. Out of 60 operative cases, 25 (41.7%) cases were operated within 3-6 hours.…”
Section: Discussionmentioning
confidence: 99%
“…Youngest age involved is 18 years and oldest one being 70 years. The most common age group affected belongs to 21-30 years forming 38.1% of the total incidence followed by 31-40years constituting 21.4% which is similar to study done by Mehta et al, Yogesh et al and Rahman et al [10][11][12] This shows that young population which is more vulnerable to RTA, thus leading to loss of young productive group of the people.…”
Section: Age Distributionsupporting
confidence: 85%
“…The most common mode of injury, following road traffic accident was found to be 78.6% which is consistent with Rahman et al with 67%, Mehta et al with 53% and Peyman et al with 80.6%. 10,11 Mehta et al says increase in the incidence of RTA is because of easily procurable of vehicles, daily migration to urban area for livelihood, unaccustomed to traffic, traffic sense and ignorance of safety measures. 11 The other mode of injury includes fall from heights which is 14.3% which is comparable to the Rahman et al As our hospital is rural based referral centre hence bull butt injuries are other mode of injury leading to the blunt trauma abdomen.…”
Section: Mode Of Injurymentioning
confidence: 99%
“…A statistically significant (P <0.001) association was found between age of patients and cause of trauma, that RTA was more common in age 20-to-70-year, Table 4. 18,19 Other studies 20 with the same findings of more young male involvement in trauma accidents found a relationship to alcohol and drug misuse in this group of victims however this influence was not studied in our study . Anarase and Anarase 18 found that RTAs were the most common cause of trauma.…”
Section: Figure 1 Frequency Of Traumamentioning
confidence: 40%